(untitled) (Jurnal Teknologi (Sciences & Engineering), 2015)
Creativity is a natural skill often exhibited by children at home and in schools, especially during play. Children are often seen playing with drawings and moulding of objects. Hence, if care is taken to encourage and develop childrenâ€™s creativity, it may enhance a sustainable development in Technical Vocational Education and Training (TVET) programme. The aim of this study therefore was to determine the level of engagement of Nigerian children in creativity practice.Â The study was carried out using 400 (232 boys and 168 girls) Junior Secondary School students of age eleven to thirteen as sample. Specifically, the study sought to find out whether or not the children do undertake creative activities at home and the domains in which their creative activities are based upon.Â A Child-Creative Inventory Form (CCIF) was used as an instrument for data collection. Data collected were analyzed using both percentages and Chi-Square. The findings of the study revealed that Nigerian children love to engage in creative activities mostly in the domain of technical and vocational skills such as: building technology, woodwork, mechanical technology, and electrical electronics. The study revealed that 87.07% of the boys were engaged in creativity while that of girls was 73.81.5%; 7.76.% of the boys were not engaged in creativity while that of girls was 20.8%. 24.57% of the boys were not sure of their involvement while that of girls was 5.36%. In all, the study found a significant difference in the level of engagement of boys and girls in creativity with P< 0.05 level of Significance. It was therefore recommended that children who are creative in the domains of technology could be assisted to develop their career in these domains as this would be a means to sustain the TVET programme in the nation.